Two-bunch operation with ns temporal separation at the FERMI FEL facility - Giuseppe Penco; Enrico Allaria; Silvano Bassanese; Paolo Cinquegrana; Stefano Cleva; Miltcho B Danailov; Alexander Demidovich; Mario Ferianis; Giulio Gaio; Luca Giannessi; Claudio Masciovecchio; Mauro Predonzani; et al. (New Journal of Physics, 2018)
In the last decade, a continuous effort has been dedicated to extending the capabilities of existing free-electron lasers (FELs) operating in the x-ray and vacuum ultraviolet regimes. In this framework, the generation of two-color (or multi-color) temporally separated FEL pulses, has paved the way to new x-ray pump and probe experiments and several two-color two-pulse schemes have been implemented at the main facilities, but with a generally limited time-separation between the pulses, from 0 to few hundreds of fs. This limitation may be overcome by generating light with two independent electron bunches, temporally separated by integral multiples of the radio-frequency period. This solution was investigated at FERMI, measurements and characterization of this two-bunch mode of operation are presented, including trajectory control, impact of longitudinal and transverse wakefields, manipulation of the longitudinal phase space and finally a demonstration of suitability of the scheme to provide extreme ultraviolet light by using both bunches.